Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Guru dan Tenaga Kependidikan SMA Negeri 11 Padang - Leni Sandra; Febsri Susanti (Lembaga Yasin AlSys, 2025)
Teacher and education personnel performance is a crucial factor in achieving educational goals, yet it is often influenced by various internal and external factors. This study aims to analyze the influence of principal leadership style and work motivation on the performance of teachers and education personnel at SMA Negeri 11 Padang. A quantitative approach was used, employing Partial Least Squares - Structural Equation Modeling (PLS-SEM) through the SmartPLS 4.0 software. The research sample consisted of 52 respondents, teachers and education personnel selected through total sampling. Data were collected using a Likert-scale questionnaire that had undergone validity and reliability testing. The analysis results indicate that leadership style does not have a significant effect on performance, whereas work motivation has a positive and significant effect on the performance of teachers and education personnel. These findings suggest that in the context of SMA Negeri 11 Padang, work motivation is the dominant factor influencing performance, while the principal’s leadership style is not a primary determinant. The implications of this study underscore the importance of strengthening work motivation through strategies such as improving welfare, providing competency development training, and fostering a supportive work environment.